Use of non-fungible tokens in operations and supply chain management - Helo, Petri; Hao, Yuqiug; Gunasekaran, Angappa (Taylor & Francis, 2025)
Non-fungible tokens (NFT) are secured storage methods for unique and non-interchangeable data items. While NFTs are commonly associated with digital arts and the cryptocurrency market, the paper explores their potential in industrial applications, particularly within operations and supply chain management. The paper introduces the technology and key processes of NFTs, providing a foundation for understanding their application in operations and supply chains. The design science method is employed by conducting requirement collection with a small group of experts and based on this a set of potential applications for operations and supply chain management is outlined. Five use case applications are presented from the requirements management point of view. The artefact developed in the process is a sample implementation, demonstrating how NFTs can be practically employed to address specific operational requirements. The results indicate that physical components, digital assets, uniqueness of the entity, contracts, security, and multiple stakeholders collectively enable various use cases where NFTs can provide value.
Keywords: blockchain; information technology; operations; supply chain; non-fungible tokens; supply chains; blockchains; fi=Tuotantotalous|en=Industrial Management|